Research on Stability of the High-order System Based on the Routh Criterion and Dominant Pole Method - Lin Xianxin; Su Qian; Ye Chengbao; Li Guojin; Liang Lin (Jixie chuandong)
The force model of the omnidirectional robot moving on the slope is constructed, the system function of the model is calculated, and the influence on the system due to load, slope θ, inertia and other disturbances is analyzed. The Routh criterion is proposed as the stability condition of the high-order system, and the root-locus dominant pole method is used to obtain a similar second-order system. The system performance index is observed and the optimal solution is obtained. The simulation results show that when the load K is 3.25 kg, the self-correction effect of the omni-directional robot on the slope motion system is better, which shows that using the Routh criterion and dominant pole method to study the stability of the high-order system is feasible and effective, and it provides a certain reference for future research on high-order system correction under the disturbance of the variable θ.